Psycho-social adjustment of the children of overseas filipino workers in the University of Northern Philippines - Pacquing, Honeylyn Galace (Vigan City, Ilocos Sur: [s.n.], 2006)
This research study attempted to determine the level of Psycho-Social Adjustments of the Children of Overseas Filipino Workers (OFWs) in the University of Northern Philippines for school year 2003-2004.
Bibliography : p. 74-76
CHED-La Union
Keywords: Children